COMPARISON OF HEALTH ANXIETY IN PSYCHIATRY AND NEUROLOGY SETTINGS - AMJAD, N; IKRAM-UL-HAQ, M; MAZHAR, N; MUSSADIQ, K; SAJIDA, I; MALIK, AA (Biological and Clinical Sciences Research Journal, 2022)
The aim of this study is to assess clinical correlates and prevalence of health anxiety in psychiatry and neurology outpatient clinic. A Prospective study was carried out at Neurology and psychiatry Department of Nishtar Medical Hospital from July 2020 to July 2021. Demographic data, clinical symptoms, comorbidities and diagnosis was recorded. Patients were given general hypochondriasis subscale of Illness Behavior Questionnaire and Short Health Anxiety Inventory (SHAI). Epi-info 7.013 was used for data entry and Stata 12.14 was used for data analysis. The prevalence of health anxiety in neurology and psychiatry was 18% and 26%, and overall prevalence was 21%. Higher health anxiety was reported in subjects with higher education, it may be due to increased awareness about illness. Health anxiety was higher in skilled workers as compared to semi skilled. The health anxiety was higher in subjects with more than one diagnosis as compared to those with single diagnosis Health anxiety is common in neurology and psychiatry settings. Further evaluation is needed to evaluate its effects on health consultation.